Discovering and Uncovering - Barry Chametzky (Grounded Theory Review: An International Journal)
Dissociative identity disorder is not new. Yet, there exists a paucity of emic research on the topic due to its covert nature. In this research, the disorder is presented and understood from the perspective of the person who must live with it on a daily basis. Through the newly discovered theory of discovering and uncovering, the reader will gain a more nuanced perspective of the disorder.